THEORETICAL ANALYSIS OF THE GITTW MODEL TO IMPROVE ENGLISH LITERACY IN INCLUSIVE SCHOOL - Ro'ifah, Ro'ifah; Pratiwi, Vina Erni; Syakroni, Moch. (TELL - US JOURNAL, 2025)
Inclusive education requires a learning approach that can accommodate the diversity of students' abilities in developing English literacy skills. However, the limitation of adaptive pedagogical models is still a major obstacle in inclusive schools, especially bridging the abilities gap between regular students and students with special needs. This study aims to theoretically analyse the GITTW (Group Investigation Think Talk Write) learning model and develop a conceptual framework for its application in strengthening English literacy. This research approach uses a literature review and preliminary interviews with teachers and inclusion coordinators at SMA Muhammadiyah 10 Surabaya. Theoretically, the GITTW model is combined from the collaborative approach of Group Investigation and the reflective-linguistic approach of Think Talk Write that is in line with Universal Design for Learning (UDL) principles where the students can engage, receive, and express learning. Initial findings indicate GITTW is considered potential to increase students’ active participation, reflective understanding, and written expression adaptively. Teachers positively responded this model flexibility to accommodate students with special needs, including dyslexia, slow learners, ADHD (attention deficit hyperactivity disorder), and concentration disorders. This study provides a theoretical basis and direction for developing more inclusive, structured, and transformative English learning practices.